A figura de Sócrates segundo Pierre Hadot - Oliveira, Loraine (Revista Archai, 2016)
This article aims to show how the figure of Socrates was analised by Hadot as a fundamental piece of his thesis about philosophy as a way of life. Here Socrates is studying from the point of view of two of his masks, that of Silenus and Eros. Hadot utilised the idea of the masks to trace the figure of Socrates. The mask of Silenus enables us to understand the atopia of Socrates. This strangeness of philosophy, goads the interlocutor into the path of dialectics. The mask of Silenus hides the socratical irony, but the heart of irony observes the meeting between Silenus and Eros. The mask of Eros permits the philosopher to define himself as a philosopher, assisting the interlocutor to discover the truth of beauty and bring it forth. Keywords: Silenus, Eros, irony, maieutics, way of life.